Quadrupling inhaled glucocorticoid dose to abort asthma exacerbations - McKeever, Tricia; Mortimer, Kevin; Wilson, Andrew; Walker, Samantha; Brightling, Christopher; Skeggs, Andrew; Pavord, Ian; Price, David; Duley, Lelia; Thomas, Mike; Bradshaw, Lucy; Higgins, Bernard; et al. (Massachusetts Medical Society, 2018)
BACKGROUND Asthma exacerbations are frightening for patients and are occasionally fatal. We tested the concept that a plan for patients to manage their asthma (self-management plan), which included a temporary quadrupling of the dose of inhaled glucocorticoids when asthma control started to deteriorate, would reduce the incidence of severe asthma exacerbations among adults and adolescents with asthma.